Nursing and breastfeeding: an eldest practicies combination - Silva, Isília Aparecida (Revista da Escola de Enfermagem da USP, 2000)
Support for breastfeeding, one of the factors contributing to mother-child wellbeing, has increased through innumerable government and non-government iniciatives. Despite this, women still have difficulty finding specialised help to solve problems related to breastfeeding and lactation after discharge from hospital. We describe the Domiciliary Attendance to Mother and son, whose aim it is to give assistance and advice to mothers in their homes. This assistance consists of teaching simplified breastfeeding management techniques, based on the Symbolic Interactionism Model. All the women assisted under this program have been able to continue breastfeeding or to re-lactate succes fully.